Unraveling the Enigma of Androcalymma (Fabaceae: Dialioideae): The Rediscovery of a Critically Endangered Legume Genus in the Heart of the Amazon - Falcão, Marcus José De Azevedo; Sousa Da Silva, Guilherme; Cardoso Pederneiras, Leandro; de Freitas Mansano, Vidal (Phytotaxa, 2023)
Androcalymma Dwyer, a monospecific and morphologically unique genus on the legume subfamily Dialioideae, stands out as one of the less known genera of Fabaceae, not being molecularly sampled in phylogenetic studies of the family until now, which led to an uncertain position among other taxa in its clade. Androcalymma glabrifolium, endemic to a small and hardly accessible area in the Brazilian Amazon rainforest, was collected once in 1936 and never seen after that, even being conjectured as possibly extinct. Here we describe a recent expedition searching for this enigmatic and rare tree that brought to light an extant population of the species in an indigenous area where it still thrives. The fruits of Androcalymma are here described and illustrated for the first time, as also its flowers’ colors and several other new characters. Here we present its first photographic register, and its DNA is compared to other Dialioideae bringing a solid relationship with the also Amazonian genus Dicorynia, a grouping sustained here by many known and newly discovered morphological characteristics. SEM analyses of flowers and fruits, conservation assessments indicating the critically endangered situation of the genus, taxonomic descriptions, and geographic, systematic, and ecological comments are made.